Cobalt carbonyl-catalyzed carbonylation of functionalized aziridines to versatile β-lactam building blocks. Issue 22 (22nd May 2017) - Piens, Nicola; Van Hecke, Kristof; Vogt, Dieter; D'hooghe, Matthias
Abstract : Aziridine to azetidin-2-one carbonylation as a convenient entry to pyrrolidines, C -fused bi- and tricyclic β-lactams and monocyclic carbapenem analogs. Abstract : The Co2 (CO)8 -catalyzed carbonylation of different classes of non-activated aziridines with diverse substitution patterns was investigated. Special attention was devoted to selectivity issues and reaction optimization. This study resulted in the regio- and stereospecific synthesis of 24 novel β-lactam target structures in high yields on a multigram scale. The synthetic potential of the newly obtained azetidin-2-ones was illustrated via ring-expansion, ring-closure, and/or side chain-functionalization protocols to provide a straightforward entry to novel pyrrolidines, C -fused bi- and tricyclic β-lactams and monocyclic carbapenem analogs.